Experience, awareness, and perceptions about medical emergencies among dental interns of Chennai city, India - L Leelavathi; V Chandrasekhara Reddy; Chaly Preetha Elizabeth; Indra Priyadarshni (Wolters Kluwer Medknow Publications, 2016)
Introduction: Every dental health professional should have the essential knowledge to identify, assess and manage a potentially life-threatening situation. Aim: To assess the experience, awareness, and perceptions about medical emergencies among dental interns in Chennai city, India. Materials and Methods: A cross-sectional study carried out in four randomly selected dental colleges of Chennai city. Data were collected using a self-administered, structured, closed-ended 20-item questionnaire. It consists of questions on experience of medical emergencies encountered by interns during their graduation, awareness of the essential drugs and equipment, the amount of medical emergencies training undertaken by participants, preparedness of interns in handling medical emergencies. Descriptive statistics, independent sample t-test, were used. Results: Out of 335 interns, 157 (47%) said that syncope was the most common medical emergency event encountered by the interns. Regarding awareness about essential drugs, about 161 (48%) study participants answered oxygen, epinephrine, nitroglycerin, antihistamine, salbutamol, and aspirin as emergency drugs. About half of the study participants, 187 (56%) were aware that pressure should be given to the affected site, with or without suturing if the greater palatine artery is inadvertently cut. The majority of the interns (93%) preferred to have a specified training on the handling of medical emergencies in dental practice. Conclusions: Syncope was the most common medical emergency event. Awareness about the essential drugs, equipment, and preparedness of dental interns in handling medical emergencies was low.